1986
DOI: 10.1016/0014-5793(86)81445-4
|View full text |Cite
|
Sign up to set email alerts
|

Common domain structure of Ca2+ and lipid‐binding proteins

Abstract: The phospholipaseAz inhibitor, lipocortin, shares common sequences with three abundant Ca2+-regulated membrane binding proteins of unknown function which are present in many cell and tissue types. A twodomain model for the structure of lipocortin is described and it is suggested that the new Caz+-regulated proteins each contain at least one lipocortin domain. The structural and biochemical properties of each protein indicate that they all directly interact with phosphohpids.Potential sites of interaction with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
49
0
1

Year Published

1986
1986
2010
2010

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(53 citation statements)
references
References 32 publications
3
49
0
1
Order By: Relevance
“…We also examined the N-terminal region and found that both S47 and D166 catalytic dyad residues located within the ␣ -␤ hydrolase fold are critical for TAG hydrolysis within cells and in vitro. Within the proximal N-terminal region, we identifi ed two overlapping motifs, a glycine-rich motif and an amphipathic ␣ -helix that are predicted by sequence analysis to be neutral lipid substrate-binding domains ( 16,17 ). We show by site-directed mutational analysis that this region, especially the amphipathic ␣ -helix, is critical for TAG hydrolysis.…”
Section: Confocal Microscopymentioning
confidence: 93%
See 1 more Smart Citation
“…We also examined the N-terminal region and found that both S47 and D166 catalytic dyad residues located within the ␣ -␤ hydrolase fold are critical for TAG hydrolysis within cells and in vitro. Within the proximal N-terminal region, we identifi ed two overlapping motifs, a glycine-rich motif and an amphipathic ␣ -helix that are predicted by sequence analysis to be neutral lipid substrate-binding domains ( 16,17 ). We show by site-directed mutational analysis that this region, especially the amphipathic ␣ -helix, is critical for TAG hydrolysis.…”
Section: Confocal Microscopymentioning
confidence: 93%
“…5F ), suggesting that the G14 residue may play an indirect role in TAG hydrolysis in living cells, possibly by participating in interactions with other cellular proteins. The second motif consists of the octapeptide FL G V YHIG, corresponding to amino acids [17][18][19][20][21][22][23][24], that is a nonconsensus version of the sequence FL X L XXXn, where X = any residue except proline and n = a nonpolar residue ( Fig. 5C ).…”
Section: Immunoblottingmentioning
confidence: 99%
“…Some key residues in this site have been identified by site-directed mutagenesis of human factor IX (Handford et al, 1991). A further calcium-binding unit, the endonexin fold, has been identified in such proteins as calelectrin and lipocortin (Geisow, 1986), and involves up to 70 amino acid residues in a calcium-dependent phosphate-binding site. Although the calcium-binding sites of these groups are not fully characterized they are unlike the repeats of the ARP.…”
Section: Transcription and Translation Of Artp In Vitvo And Import Inmentioning
confidence: 99%
“…Calelectrin was initially described in the electric organ of Torpedo marmorata and later in mammalian tissues, as a protein able to bind calcium and chromaffin granule membranes, and was considered as a candidate for Ca 2+ dependent Correspondence address: H. van den Bosch, Biochemistry Laboratory, Padualaan 8, 3584 CH Utrecht, The Netherlands regulators of membrane events [11][12][13]. The lipocortins, the calpactins and the calelectrins all possess a 17 amino acid residue consensus sequence [14][15][16].…”
Section: Introductionmentioning
confidence: 99%